A Race Against Death: Peter Bergson, America, and the Holocaust, David S. Wyman and Rafael Medoff (New York: The New Press, 2002), 269 pp., cloth 26.95, pbk. 17.95 - Schwartz, Donald R. (Holocaust and genocide studies, 2005)
In some respects, this is a tragic and sordid saga of a timid and fainthearted American Jewish establishment incapacitated by fear. The title of this book could easily have been The Abandonment of the Jews ... by American Jews, to borrow from David Wyman’s earlier work. But in another sense, it is a heroic, uplifting chronicle of an individual’s most extraordinary, valiant struggle against almost insurmountable obstacles. The focus of the book is Hillel Kook, nephew of the chief rabbi of Palestine, who made it his life’s mission to persuade and encourage the United States to intervene on behalf of European Jews during World War II.